Wahyu Hidayat's Terrorism Financing Deradicalization Strategy - Ika Veni Anisa; Muhamad Syauqillah (International Journal of Science and Society, 2023)
The deradicalization programme is mandated by Law No. 5/2018, especially in approaching prisoners of terrorism. The deradicalization programme is carried out so that prisoners abandon their acts of violence and crime and even abandon radical thoughts or ideologies. This programme is implemented both inside and outside the prison. This research reveals the deradicalization program experienced by terrorism convict Wahyu Hidayat. This research is qualitative research with a case study research type. The primary data in this research are interviews with Wahyu Hidayat, Densus 88 Anti-Terror Polri investigators and BNPT deradicalization personnel. The results of this research show that, currently, the disengagement program for Wahyu Hidayat has succeeded in making him leave his group, Wahyu Hidayat is still in prison in the stage of developing his identity and social reintegration with various programs. Based on this, the rapid change in Wahyu Hidayat's attitude needs to be a precaution for BNPT in conducting identification as an initial stage of deradicalization, as well as the need for a sustainable program to ensure Wahyu Hidayat does not re-offend.